2018
DOI: 10.3892/mco.2018.1670
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of 18F-fluorodeoxyglucose positron-emission tomography/computed tomography ground-glass nodule findings

Abstract: F-fluorodeoxyglucose positron-emission tomography/computed tomography (F-FDG-PET/CT) is important in lung cancer diagnosis; false negatives are often caused by ground-glass nodules (GGNs). PET/CT utility in GGN diagnosis is unknown. The associations between GGN CT findings (size, properties), the pathological diagnosis and maximum standardized uptake value (SUV) were explored. Sixty-six patients with pathological stage IA1-IIA lung adenocarcinoma underwent surgical resection and PET/CT between January 2010 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…In this study, we found that PET semi-quantitative parameters can be used as noninvasive imaging surrogates to distinguish between MIA and IA ( Fig. 2 ), which is consistent with several previous studies [ 24 25 26 ]. Notably, PET semi-quantitative parameters have the capability to differentiate AIS from MIA ( p < 0.05), especially for persistent pure GGN lesions.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we found that PET semi-quantitative parameters can be used as noninvasive imaging surrogates to distinguish between MIA and IA ( Fig. 2 ), which is consistent with several previous studies [ 24 25 26 ]. Notably, PET semi-quantitative parameters have the capability to differentiate AIS from MIA ( p < 0.05), especially for persistent pure GGN lesions.…”
Section: Discussionsupporting
confidence: 91%
“…Other PET-CT results confirm previous investigations. 38 This study reveals a significant association between both the visual analysis of FDG uptake (Table 3) and the visual FDG uptake and the selected pleural invasion on histologic section (p ¼ 0.001). The SUV max values found in the present study cannot be directly compared with those in the study of Tanaka et al, 37 as in our study, the acquisition of the images was started 60 minutes postinjection (in the study of Tanaka et al, 37 this was 90 min).…”
Section: Discussionmentioning
confidence: 57%
“…In other studies, the false negativity rate of malignant pure GGN has been reported as high as 90-100% [13][14][15][16], which is thought to be because of the high proportion of <1-cm nodules [13,21] or the strict criterion of [ 18 F]-FDG uptake positivity (a SUV max ≥ 2.5 [14] or a higher [ 18 F]-FDG uptake than that of mediastinal blood pool activity [15]). To avoid high false negativity rates due to small size or a high standard of positive criteria, we evaluated only pure >1-cm GGNs and set the positivity criteria to be [ 18 F]-FDG uptake higher than background lung activity in visual analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that non-small cell lung cancer (NSCLC) expressed as subsolid nodules has lower [ 18 F]-FDG uptake than other types of NSCLC. In particular, the false-negative rate of a malignant pure GGN has been reported as high as 90-100% [13][14][15][16]. One of the reasons for the low [ 18 F]-FDG uptake of malignant subsolid nodules is that [ 18 F]-FDG is not distributed in the air portion within the nodule, which may underestimate the [ 18 F]-FDG uptake of the solid portion.…”
Section: Introductionmentioning
confidence: 99%